On fairness and application performance of active queue management in broadband cable networks - Hong, Gongbing; Martin, James; Westall, James M. (Computer networks (Amsterdam, Netherlands : 1999), 2015)
We evaluate the performance of modern delay-based active queue management (AQM) algorithms in downstream DOCSIS 3.0 cable environments. Our simulation-based study involves scenarios that include tiered service levels and application workloads that include FTP, HTTP-based adaptive streaming (HAS), VoIP, and web traffic. Our results show that AQM maintains target queuing delays and consequently provides strong isolation between responsive high bandwidth and low bandwidth latency sensitive flows. We also show that lowering target queuing delays exacerbates TCP’s RTT unfairness. Nevertheless, in the scenarios that we studied, observed application performance was not significantly impacted by the specific AQM in use. With the potential large deployment of AQM imminent for DOCSIS 3.0, the analysis presented in this paper provides timely feedback to the community concerning how delay-based AQM can manage bandwidth allocation fairness and application performance in realistic downstream DOCSIS 3.0 cable network systems.